Imprecision in the Era of Precision Medicine in Non-Small Cell Lung Cancer - Sundar, Raghav (Front Med (Lausanne), 2017)
Over the past decade, major advances have been made in the management of advanced non-small cell lung cancer (NSCLC). There has been a particular focus on the identification and targeting of putative driver aberrations, which has propelled NSCLC to the forefront of precision medicine. Several novel molecularly targeted agents have now achieved regulatory approval, while many others are currently in late-phase clinical trial testing. These antitumor therapies have significantly impacted the clinical outcomes of advanced NSCLC and provided patients with much hope for the future. Despite this, multiple deficiencies still exist in our knowledge of this complex disease, and further research is urgently required to overcome these critical issues. This review traces the path undertaken by the different therapeutics assessed in NSCLC and the impact of precision medicine in this disease. We also discuss the areas of “imprecision” that still exist in NSCLC and the modern hypothesis-testing studies being conducted to address these key challenges.